Distant Territory and Ensayos Pedagógicos - Blanco, Lidia (2003)
The reflection, analysis, criticism, and deepening of the different topics that are dealt with in our societies are an obligatory task if we want to remain lucid in the face of the permanent manipulation of these topics by the different powers.